Comparative Study of RC Frame Building with NBC 105:2020 and IS Code 1893:2002 (International Journal of Innovative Research in Engineering & Management, 2022)
Construction is a vital part of every  developing country in this era. Every country has specific  building design codes which provide the standards to  engineers for the design of various structural components  like beam, column and slab. RC building design of every  country is based on their geographical location. In today  world of globalization, an engineer must be efficient to  understand and handle codes of various countries.  Considering this the main focus of this research work is to  bring out differences and similarities between different RC  design codes and to use it to develop a common platform.  In this research RC design code of NEPAL, INDIA are  considered. The main focus is the relative gains and  shortcomings of various buildings design codes under  certain criteria like loading analysis, design analysis, ease  of use and economical point of view. Several parameters for  different cross-section and different building material on  basis of strength are considered. Comparison work has  worked out on the basis of loading comparison like live  load, dead load, wind load and different parameters for  various elements of the building such as beam, column and  slab. Load factor and load combination are also compared.  This comparison investigates the design capacities for  various building design codes.In present study RCC  building models having G+8 stories with regular plan is  considered for analysis. The analysis of model is done using  equivalent static method in ETABS software.
Keywords: Base shear; Storey Shear; Seismic Analysis; Storey Drift